Traits of German Symbolism - Kastins, Juris (Revista de Filología Alemana, 2011)
This article contains as an introduction the basic premise of French symbolism, and the extent of its importance in understanding the poetics of Hugo von Hofmannsthal and Stefan George (especially examples of Mallarmé and some principles by Baudelaire). Subsequently, Hofmannsthal’s ideas on modern poetry are analysed in detail, especially with the help of the famous “Gespräch” between Clemens and Gabriel - two fictional characters, who differ in their opinions on the nature of poetry. The final section discusses both Stefan George’s poetics maxims and some examples of his poetry. Finally, the difference between the German and French Symbolism is briefly discussed.
Keywords: French Symbolism; German Symbolism; literary influence; literary contrast; Hugo von Hofmannsthal; Stefan George.